Opportunities for breaking 43 seconds in the men's 400m - Stoyanov, H. (New Studies in Athletics, 2016)
Wayde van Niekerk's sensational victory and world record in the men's 400m at the 2016 Olympic Games has excited experts and the public with the prospect that he or one of a strong field of rivals could soon run the distance in less than 43 seconds. What will it take in terms of physical capability and effort distribution in the race for someone to achieve this goal? And what effect might the lane draw have on high-level 400m competitions and performances? This study draws on existing data to address these questions and add to the current conversation on the development of the 400m. After reviewing research on the effects of running on the bends, the author examines the velocity dynamics of the men's 400m medallists in selected IAAF World Championships in Athletics over the last two decades and confirms the importance of the 200-300m segment of the race. He also compares van Niekerk's performance with the previous record by Michael Johnson (USA) and suggests that van Niekerk could profit from improving his performance in the 200m if he wishes to achieve faster times over 400m.